An educator's toolkit for virtual simulation: A usability study. (December 2022) - Verkuyl, Margaret; Taplay, Karyn; Job, Treva; O'Keefe-McCarthy, Sheila; Atthill, Stephanie; Goldsworthy, Sandra; Atack, Lynda
Abstract: Background: The rapid change brought on by COVID-19 meant that many educators adopted virtual simulation quickly, often without having a strong background in the pedagogical principles of virtual simulation. To address this resource gap, a team of 21 Ontario virtual simulation-experienced educators created the freely available, online, interprofessional Virtual Simulation Educator's Toolkit. The Toolkit provides the theory, practical strategies and resources needed to teach effectively with virtual simulation. Because the Toolkit would include new content, resources and numerous untested design elements, the team conducted a usability test. Design: A usability study, that followed a three-step process, was conducted. Participants were asked to carefully review the Toolkit, including all interactive components and complete an online survey based on the Technology Acceptance Model, to measure the ease of use and utility of the Toolkit. Lastly, participants were interviewed. Participants: In keeping with sampling principles for usability studies, twenty experienced virtual simulation educators from different disciplines participated in the study. Methods: A validated survey and one-on-one interviews were used to measure educators' perceptions of the ease of use and utility of the Toolkit and their recommendations to improve it. Quantitative data were analyzed using descriptive statistics and qualitative data were coded and themes developed. Conclusion: The score of 90 % on the Toolkit Experience Survey indicated that participants found the Toolkit both easy to use and useful. Results from the interviews indicated that a practical, accessible professional development tool is urgently needed to support education with virtual simulation. Because the Toolkit introduces educators to different ways of implementing virtual simulation, as well as options, process considerations, and tools to enhance their teaching with virtual simulation, different disciplines and educators with different levels of simulation experience may benefit by using it. Highlights: The pandemic resulted in rapid adoption of virtual simulation. Many educators were unprepared for virtual simulation adoption. A freely available, online, Virtual Simulation Educator's Toolkit was developed. Usability testing of the Toolkit demonstrated the Toolkit is easy to use and useful. Novice to advanced level virtual simulation educators may benefit from the Toolkit.